C.G. Jung's autobiography as a source of information on his psychohistory an evaluation. [article]. - Tilander, Ake
The problem we discuss in this article is if, and to what extent, it is possible to use C.G. Jung's autobiography "Memories, Dreams, Reflections" as a means to understanding and describing his psychological development. As an instrument of our analysis, we have used Gordon W. Allport's table of 13 different reasons for an author to write an autobiography. By clarifying C.G. Jung's reasons we believe that it is possible to evaluate the autobiography as a source of information. Our main conclusions are: first , the chapter concerning C.G. Jung's relation to Sigmund Freud is clearly biased and apologetic, C.G. Jung gives his view of the conflict, but if the chapter is treated as C.G. Jung's subjective description we gain valuable information. Secondly, C.G.Jung try ti give a description of the psychological experiences in his life rather than of external events. Compared to other similar document, this makes the autobiography less valuable to the historian, but more valuable to the psychologist. C.G. Jung's subjective experiences are intimately connected to his theories. In one sense we can say that the experiences are the empirical form form of the theories. However, we have shown that the experiences have been structured in a theoretical form. The substance of the experiences seems to have been influence to a lesser degree. When using these experiences as source material we have to take the retroactive influence of C.G. Jung's theories into account. Thirdly. we have pointed out that even if Jaffe' held the pen when major parts of the autobiography were written, this has had very little effect on the contents of the autobiography. Our general conclusion is that if these obstacles are taken into account, the autobiography is very useful in a psychological analysis of C.G. Jung's psycho-history.